Epigenetic regulation of stem cells in lung cancer oncogenesis and therapy resistance - Wu, Jiayang; Feng, Jiaming; Zhang, Qiran; He, Yazhou; Xu, Chuan; Wang, Chengdi; Li, Weimin (Frontiers in Genetics, 2023)
Epigenetics plays an important role in regulating stem cell signaling, as well as in the oncogenesis of lung cancer and therapeutic resistance. Determining how to employ these regulatory mechanisms to treat cancer is an intriguing medical challenge. Lung cancer is caused by signals that cause aberrant differentiation of stem cells or progenitor cells. The different pathological subtypes of lung cancer are determined by the cells of origin. Additionally, emerging studies have demonstrated that the occurrence of cancer treatment resistance is connected to the hijacking of normal stem cell capability by lung cancer stem cells, especially in the processes of drug transport, DNA damage repair, and niche protection. In this review, we summarize the principles of the epigenetic regulation of stem cell signaling in relation to the emergence of lung cancer and resistance to therapy. Furthermore, several investigations have shown that the tumor immune microenvironment in lung cancer affects these regulatory pathways. And ongoing experiments on epigenetics-related therapeutic strategies provide new insight for the treatment of lung cancer in the future.